THE THE EVALUATION OF PATTERN OF WHOLE BLOOD DONOR DEFERRALS IN A TERTIARY CARE CENTER OF NORTH INDIA - BASSI, RAJNI; SINGAL, POONAM; KAUR, LIVELEEN; KAPOOR, URVASHI; BANSAL, SUKRITI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Donor recruitment is critical to the supply of safe and adequate blood/blood components to meet patient’s need; the first and most crucial step to provide safe blood is proper selection of blood donors. Blood donor selection criteria are designed to ensure the donor as well as the recipient’s health. The objective of this study is to analyze the various causes of donor deferral, study their frequency pattern and to suggest changes to retain and retrieve donors in future. Methods: A retrospective study on analysis of deferred donors of whole blood was conducted in a blood center at tertiary care hospital in North India. The study included blood donors deferred from January 2022 to December 2022. Results: A total of 27,121 donors were registered for whole blood donation and 4534 (16.71%) were deferred. Female deferral (41.67%) was more as compared to male deferral (15.11%). Temporary deferrals (n=4238 [93.47%]) were significantly higher than permanent deferrals (n=296 [6.5%]). The most common reason for temporary deferral was anemia (n = 940 [20.7%]) while that for permanent deferral was jaundice (n=179 [3.94%]). Conclusion: Analyzing the causes, frequency and deferral pattern of blood donors will help to guide the recruitment and retention efforts to maintain a healthy donor pool at large.